2018
DOI: 10.3389/fgene.2018.00512
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Post-transcriptional Control: Better Living Through RNA Regulons

Abstract: Traditionally, cancer is viewed as a disease driven by genetic mutations and/or epigenetic and transcriptional dysregulation. While these are undoubtedly important drivers, many recent studies highlight the disconnect between the proteome and the genome or transcriptome. At least in part, this disconnect arises as a result of dysregulated RNA metabolism which underpins the altered proteomic landscape observed. Thus, it is important to understand the basic mechanisms governing post-transcriptional control and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 94 publications
1
24
0
Order By: Relevance
“…Together these data raise the possibility that motif 2 mediates localization of a cohort of mRNAs that encode proteins that function in distal ends of cellular projections, implicating the motif as a mRNA regulon. RNA regulons are primary sequences or secondary structures that are co-regulated at the post-transcriptional level to coordinate cellular functions (71)(72)(73)(74). Identification of the trans-acting factors that interact with the motifs we identified will provide future insights into the molecular functions of myelin sheath growth, which will lead to a more complete understanding of the mechanisms guiding developmental myelination.…”
Section: Localization Motifs Are Enriched In the Myelin Transcriptomementioning
confidence: 93%
“…Together these data raise the possibility that motif 2 mediates localization of a cohort of mRNAs that encode proteins that function in distal ends of cellular projections, implicating the motif as a mRNA regulon. RNA regulons are primary sequences or secondary structures that are co-regulated at the post-transcriptional level to coordinate cellular functions (71)(72)(73)(74). Identification of the trans-acting factors that interact with the motifs we identified will provide future insights into the molecular functions of myelin sheath growth, which will lead to a more complete understanding of the mechanisms guiding developmental myelination.…”
Section: Localization Motifs Are Enriched In the Myelin Transcriptomementioning
confidence: 93%
“…Interestingly, these RNAs encode proteins or participate in RNA-related processes, such as RNA binding or mRNA transport (Figure 2C), adding another layer to the RNA regulon model: interacting RBPs that regulate RNAs implicated in RNA-associated processes. In fact, 30% of these common targets ( n = 19) are also RBPs (Figure 2C) (Culjkovic-Kraljacic and Borden, 2018). However, some well-known cancer driver genes, such as MYC and COX-2 are common targets of 11 and 7, respectively out of 18 CRC RBPs.…”
Section: Common Features Of All Colon Cancer Related Rbpsmentioning
confidence: 99%
“…As a consequence, it can elevate the production or alter the form of proteins that function in survival, proliferation, migration, invasion and metastases. Often, networks of RNAs encoding proteins involved in the same biological process, known as RNA regulons, are disrupted simultaneously, leading to a wide array of biological changes supporting disease phenotypes [ 2 , 3 ]. Several studies demonstrated that RNA processing, including dysregulated RNA export and translation, can contribute to aberrant control of RNA regulons thereby driving human diseases such as cancer and neurodegenerative conditions [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, eIF4E overexpression leads to increased numbers of ribosomes per transcript on a select group of RNAs thereby elevating translation efficacy. Many of these transcripts encode proteins involved in oncogenic RNA regulons [ 2 ]. Indeed, eIF4E is elevated in a wide variety of cancers and eIF4E has been targeted in multiple cancer clinical trials [ 43 47 ] (see cancer section).…”
Section: Introductionmentioning
confidence: 99%